The Strategy of Qur'an Teachers in Improving Students' Qur'an Reading Skills at TPQ Lendang Terak, Ekas Buana Village, Jerowaru District - Sirajun Nasihin; Rosidi Sopianto (Journal of Islamic Religious Studies, 2025)
This study aimed to describe the strategies employed by religious teachers to improve students’ Qur’an reading abilities at the Lendang Terak Qur’anic Education Park (TPQ), located in Ekas Buana Village, Jerowaru District. A qualitative research method with a descriptive approach was applied. Data were collected through observation, interviews, and documentation, involving religious teachers and students as the primary data sources. The data were analyzed using the Miles and Huberman model, which included data reduction, data display, and conclusion drawing. The findings revealed that teachers implemented a range of strategies, including gradual and individualized guidance, the talaqqi method, motivational techniques, personal approaches, and the use of simple learning media tailored to students’ varying levels of ability. Several internal and external factors were found to influence the effectiveness of these strategies. Internal factors encompassed intelligence, talent, interest, motivation, and students' ability to maintain focus during learning. Students with higher cognitive abilities and motivation were generally quicker in acquiring Qur’an reading skills. External factors included parental involvement, environmental support, availability of facilities, and the teacher’s role. The study also identified key challenges such as limited infrastructure, insufficient instructional time, and lack of support from families and the broader environment. Conversely, the presence of qualified teachers, engaging teaching methods, and a religiously conducive environment significantly contributed to enhancing students’ reading proficiency.